Multimodality In “Bakiak Games” Posts on G20 2022 Social Media - Ahmadi F, Yusep; Syaifullah, Aceng Ruhendi; Hermawan, Budi (LPPM IAIN Parepare, 2024)
This study aims to reveal the meaning of the message in the multimodal post